D10.8 Data Management Plan, WP10 - Neocleous, Kyriacos; Themistocleous, Kyriacos; Papoutsa, Christiana (My University, 2020)
The aim of the Data Management Plan is to outline the data management policy of the EXCELSIOR Phase II Teaming Project, and elaborate the appropriate framework for access, use and re-use of the four types of data which would be collected or generated by the EXCELSIOR Phase II Teaming Project. The Data Management Plan of the EXCELSIOR Project initially provides a summary of the four types of datasets (i.e. Communication, Scientific Publications, Deliverables and Trainings), followed by the procedures adopted to make the data discoverable, accessible, interoperable and re-useable (FAIR). The resources available to the Data Management Plan are also outlined as well as the provisions made for data security. The Data Management Plan also includes a template for describing the data, according to the H2020 recommendations.